Selection of thermophysical properties of heat storage wall - Koczyk, Halina (Journal of Civil Engineering and Management, 2002)
The paper discusses a method of the multilayered heat storage wall. Initial data: walls are multilayered, heat conductivity process is considered being one-dimensional, climatic factors and power supplied are periodic functions of time. In the paper mathematical and numerical models are presented. A mathematical model is constituted of a system of differential equations which describe heat conduction in material layers, equation of heat balance and boundary conditions system. Solving equations with regard to unknown property which has been recognized as a crucial parameter in the task one can obtain a real numeric value of the parameter. The paper is illustrated by the nomograms of calculated accumulating layer thickness and the scheme of an algorithm designed to calculate the thickness of accumulating layer. Frist Published Online: 30 Jul 2012